The energy release rate of crack growth in an irradiation-induced thermo-diffusion-mechanical (I-TDM) coupling system - Dong, Yingxuan; Zhou, Yi; Tang, Changbin; Lu, Huaiyu; Zuo, Hong (Frontiers in Materials, 2022)
Material cracking behavior in reactor is generated under the irradiation effect accompanied by thermal expansion, fission products diffusion and mechanical load. In this study, the energy release rate for crack growth under irradiation has been deduced synthetically according to the thermodynamically consistent method and numerically implemented by finite element method (FEM). Variation of the total energy was obtained based on the principle of minimum potential energy in which the dissipative behavior can be characterized by fission energy, irreversible heat flow and diffusion of fission products. Through calculating variation of the total energy with respect to crack length, the energy release rate for crack propagation was analytically represented. Additionally, the total energy release rate for deflective crack was also derived to predict crack kinking. Furthermore, numerical implementation of the presented model was performed by FEM and the equivalent domain integral method. Effects of irradiation on the physical fields and the energy release rate near crack tip were investigated and analyzed in such a complex I-TDM coupling system. This study can be developed to investigate fracture problems, assess structural integrity and evaluate material strength of irradiated materials.